Caracterização física e química dos frutos nos diferentes quadrantes da planta e germinação de sementes do portaenxerto cítrico tangerineira ‘Sunki’ - Souza, Jackson Mirellys Azevêdo [UNESP]; Modesto, Joyce Helena [UNESP]; Leonel, Sarita [UNESP]; Gonçalves, Bruno Henrique Leite [UNESP]; Ferraz, Rafael Augusto [UNESP] (My University, 2015)
The tangerine ' Sunki' are highly relevant for the Brazilian citrus industry by presenting important traits for genetic improvement and to be considered a great portaenxento. In this context, the objective of the present work to study the characterization of the fruits of citrus rootstock ' Sunki', depending on the position on the plan and also the germination of their seeds . The physical characteristics evaluated were fruit weight, longitudinal and equatorial diameters of the fruit longitudinal diameter / equatorial diameter, number of buds per fruit , weight of buds and bark and number of viable seeds per fruit. As for the chemical characterization was evaluated titratable, acidity, soluble solid, Ratio , pH and vitamin C. For the evaluation of these variables, the fruits were obtained from the northeast, southwest, northwest and southeast quadrants. Regarding the evaluation of seed germination, different doses of gibberellic acid and Stimulate were used. The seeds extracted from ripe fruit, washed, dried in the shade and stored in BOD. Immediately after, they were treated for 24 hours with plant growth regulators. After soaking, the seeds were placed in a germinator in germitest paper. After initiation of the germination process, the evaluations were performed daily until the thirty- fourth day. Fruits of 'Sunki' mandarin with uneven as the fruit position within the canopy, the use of gibberellic acid and growth promoter is promising for commercial use on seed germination of this rootstock.
Physical and chemical characterization of fruit in different plant quadrants and germination rootstock of citrus tangerine ‘Sunki’
Keywords: Bioregulators; Citrus sunki Hort; Ex Tanaka; Fruit quality; Position of the fruit in the canopy